Distinct Patterns of Interhemispheric Connectivity in Patients With Early- and Late-Onset Alzheimer’s Disease - Li, Kai-Cheng; Luo, Xiao; Zeng, Qing-Ze; Xu, Xiao-Jun; Huang, Pei-Yu; Shen, Zhu-Jing; Xu, Jing-Jing; Zhou, Jiong; Zhang, Min-Ming (Frontiers in Aging Neuroscience, 2018)
Background: Early-onset Alzheimer’s disease (EOAD) presents a different clinical profile from late-onset Alzheimer’s disease (LOAD). Neuroimaging studies demonstrated that EOAD patients present more atrophy and functional disconnection than LOAD patients. However, the changes of inter-hemispheric functional interactions and underlying structural connectivity remain unclear. Methods: This study combined resting-state functional MRI and diffusion tensor imaging to assess inter-hemispheric functional and structural connectivity in 22 EOAD patients, 28 LOAD patients and two age-matched controls correspondingly (18 relatively young and 21 old). The voxel-mirrored homotopic connectivity (VMHC) method was used to examine the inter-hemispheric functional connectivity while tract-based spatial statistics was applied to calculate the diffusion indices. Results: Compared with controls, EOAD patients had lower VMHC value in the hippocampus, parahippocampal gyrus, superior temporal gyrus, and inferior parietal cortex (IPC). Correspondingly, disruptions in posterior white matter tracts were found in EOAD patients. By contrast, LOAD patients displayed increased VMHC value and impaired white matter tracts in the frontal region. Correlation analyses showed that VMHC value in IPC was related to executive function in EOAD patients (r=-0.67, P<0.05). Conclusion: EOAD patients have more widely disrupted inter-hemispheric functional connectivity than LOAD patients, which can be significantly related to the integrity changes of white matter structures. Besides, decreased inter-hemispheric connectivity contributes to executive deficits in EOAD patients. Our study suggested that divergent damage patterns between hemispheres could possibly decipher separate clinical performance in EOAD and LOAD.